KONSEP PENDIDIKAN KARAKTER DALAM AL-QUR’AN - Abd. Mukhid (NUANSA: Jurnal Penelitian Ilmu Sosial dan Keagamaan Islam, 2016)
The kind of character problems in the Indonesian nation until now is still alarming. The various of the facts about negative character has real shown by indonesian society with the specific reason as if it has true to do it. Drugs has increasingly, corruption has widespreadly, spoliate with violence, bullying in schools, sexual crimes on the learners, students online transactional sex, domestic violence, and others. The various issues are demanding character of the Indonesian nation that character education really can create a positive character of the Indonesian nation. Given Indonesia is a Muslim majority, then there are two issues to be answered in writing this article: first, how the concept of character education in the Qur'an; and second, how the concept of character education in Islamic education.